THE VALUE OF VALUES: A GLOBAL BRAND’S ASSESSMENT ACROSS BRAZILIAN CULTURAL DIVERSITY - Añaña, Edar da Silva (2009)
This paper explores the influences of personal values and of other cultural elements in the assessment of a global brand across four Brazilian regional subcultures. It uses the Rokeach Values Survey (1968, 1973) to measure personal values, and the Brand Personality Scale, of Aaker (1997), to interpret brand attributes in a sample 308 university students and high-schooled people. Results detected significant relationship amongst personal values and the brand evaluation, and confirmed some influence of rituals, symbols and demographics in the way consumers perceive an international brand like Nike. Personal values and other cultural elements of subcultures showed significant differences that can be useful for marketing strategies intended to the specific areas of that country.